Unravel the Active Site in Nitrogen_Doped Double_Walled Carbon Nanotubes for Nitrogen Dioxide Gas Sensor - Worawut Muangrat; Winadda Wongwiriyapan; Visittapong Yordsri; Thanattha Chobsilp; Saowaluk Inpaeng; Chaisak Issro; Oleg Domanov; Paola Ayala; Thomas Pichler; Lei Shi (My University, 2018)
In this paper, a nitrogen dioxide (NO 2 ) gas sensor using nitrogen‐doped double‐walled carbon nanotubes (N‐DWCNTs) with different types of nitrogen is demonstrated, and the sensor performance to the pyridinic nitrogen is related. The ratio of nitrogen is controlled by the temperature applied for the synthesis. It is found that the fabricated sensor from N‐DWCNTs enable an approximately threefold improvement in NO 2 detection compared to the sensor from DWCNTs. Also, the improvement of sensor response of N‐DWCNTs more depends on the pyridinic site than the other types of nitrogen, because it can strongly interact with the NO 2 molecule. The sensing mechanism is attributed to the charge transfer between the NO 2 molecule and the sensing materials (especially with pyridinic site), which shifts the Fermi level, resulting in a decrease of the electrical resistance. Furthermore, the relation between the sensor response and the concentration of NO 2 is derived based on Langmuir adsorption isotherm, and the calculated detection limit can be down to 0.14 ppm, which suggests that the N‐DWCNTs‐based sensor is a promising approach for low concentration NO 2 detection at room temperature.
Keywords: Nitrogen dioxide; Carbon Nanotubes in Composites